The Value of Independent Specialty Designation for Interventional Cardiology. DOI: 10.1002/ccd.26656 - James C. Blankenship; Wayne A. Powell; Dawn R. Gray; Peter L. Duffy (Catheterization and Cardiovascular Interventions, 2017)
BACKGROUND: Aorto-ostial coronary lesions represent a high-risk subset of coronary disease because of fibrocalcific disease, elastic recoil, and difficulty achieving precise stent positioning. Percutaneous coronary intervention (PCI) of these lesions may therefore be associated with less favourable outcomes than of proximal non-ostial lesions. Furthermore, ostial left main coronary artery (LMCA) and right coronary artery (RCA) lesions differ in anatomy and myocardium at risk. AIMS: To compare procedural practice and outcomes of aorto-ostial versus proximal non-ostial PCI. METHODS: We analysed patients from the multicentre Melbourne Interventional Group Registry who underwent PCI between 2005 and 2020. Patients treated for ostial LMCA or ostial RCA lesions (aorto-ostial lesion [AOL] group) were compared with those undergoing PCI for proximal non-ostial LMCA or RCA lesions (non-AOL group). The primary outcome was long-term mortality. Secondary outcomes were in-hospital and 30-day major adverse cardiovascular events (MACE), with multivariable logistic regression used to identify independent predictors of 30-day MACE. Vessel-specific analysis compared ostial and non-ostial LMCA and RCA PCI separately. RESULTS: Among 4683 PCI procedures, 538 (11.5%) underwent PCI for AOL and 4145 (88.5%) for proximal non-ostial LMCA or RCA lesions. Patients in the AOL group were older (70.1 vs. 65.0 years, p < 0.001), more often female (37.7% vs. 25.5%, p < 0.001), and had a greater burden of comorbidity and lesion complexity. Rotational atherectomy (4.5% vs. 1.2%, p < 0.001) and intravascular ultrasound (5.9% vs. 1.2%, p < 0.001) were used more frequently in the AOL group, although overall use was low. AOL location was not independently associated with 30-day MACE (adjusted OR 0.93, 95% CI 0.60-1.45; p = 0.76). Long-term survival was lower in the pooled AOL cohort (log-rank p < 0.001); vessel-specific analysis showed no difference for LMCA PCI (p = 0.69), whereas survival was lower after ostial RCA PCI (p < 0.001). CONCLUSIONS: Patients undergoing AOL PCI had a higher-risk clinical profile but similar adjusted early outcomes. In vessel-specific analyses, the pooled long-term survival difference appeared predominantly attributable to the RCA cohort, with no difference between ostial and non-ostial LMCA PCI. This may reflect differences in baseline patient risk rather than excess periprocedural risk alone.